Heavy Metal Content in the Eyes of Yellowfin Tuna (Thunnus albacares, Saanin 1983) from Aceh Waters as Raw Material for Fish Oil Production: Kandungan logam berat mata ikan tuna sirip kuning (Thunnus albacares, Bonnaterre 1788) asal Aceh sebagai bahan baku minyak ikan - Fahri Sinulingga; Wini Trilaksani; Jidan Ramadani (Habitus Aquatica, 2026)
Yellowfin tuna (Thunnus albacares) is one of Indonesia’s leading fishery commodities, with high potential as a raw material for fish oil, especially from the eye tissue, which is rich in omega-3 fatty acids. This study aimed to evaluate the heavy metal content in yellowfin tuna eyes from Aceh waters to ensure the safety of extracted fish oil. Eye samples were obtained as by-products from a tuna fillet processing industry in Banda Aceh. Preparations were carried out by separating soft tissues from hard parts, followed by oil extraction using the cold water extraction method. Characterization included morphometric analysis and determination of heavy metal contents (Hg, Pb, Cd, As) using Atomic Absorption Spectrophotometry (AAS), based on national (SNI) and international (Codex Alimentarius 2017) standards. Results showed that Hg, Pb, and Cd were not detected, while As was present at a concentration of <0.005 mg/kg—well below safety thresholds. These findings indicate that yellowfin tuna eye oil from Aceh is safe for consumption and holds promising potential as a high-value functional food or dietary supplement ingredient.